Primary Epithelial Myoepithelial Carcinoma of Lung, Reporting of a Rare Entity, Its Molecular Histogenesis and Review of the Literature - Farzana Arif; Susan Wu; Shahriyour Andaz; Stewart Fox (Hindawi Limited, 2012)
Primary epithelial myoepithelial carcinoma of lung is a rare entity and is thought to arise from the submucosal bronchial glands distributed throughout the lower respiratory tract. Because of the rarity of this tumor, we describe one case of epithelial myoepithelial carcinoma arising in the bronchus intermedius and presenting as an endobronchial mass. A 57-year-old male patient presented with an incidental finding of an endobronchial mass located in the lumen of the right lower lobe bronchus and caused near total luminal occlusion of the bronchus. An endobronchial carcinoid tumor was entertained clinically. Subsequently the patient underwent an uneventful videothoracoscopic lobectomy of lower and middle lobes of the right lung. Morphologically and immunohistochemically the tumor was characterized by two cell populations with epithelial and myoepithelial cells forming duct-like structure. The final diagnosis of epithelial myoepithelial carcinoma of lung was rendered.